Resistant and difficult-to-treat hypertension - Jędrusik, Piotr (Przewodnik Lekarza/Guide for GPs, 2007)
Resistant hypertension is defined as blood pressure exceeding target values (e.g. 140/90 mmHg) despite the use of appropriate doses of three antihypertensive drugs including a diuretic. This review focuses on the prevalence, causes and consequences of resistant hypertension as discussed in the recent guidelines for the management of arterial hypertension published by the European Society of Hypertension and the European Society of Cardiology. The management of such patients must be based on careful clinical evaluation supplemented by ambulatory blood pressure monitoring and other laboratory testing, and should include proper antihypertensive drug combinations, simplified drug regimens, patient education, and finally referral to specialist hypertension centres.